Technical Perspective: FoundationDB Performs Balancing Act. - Kemper, Alfons (Communications of the ACM, 2023)
The article discusses the design of FoundationDB, an open-source NoSQL database, which pioneered the development of a scalable, distributed key-value system that combines high availability and low latency while guaranteeing strong consistency.